Analytical multikinks in smooth potentials - Brito, G. P. de [UNESP]; Correa, R. A. C. [UNESP]; Souza Dutra, A. de [UNESP] (Amer Physical Soc, 2014)
In this work we present an approach that can be systematically used to construct nonlinear systems possessing analytical multikink profile configurations. In contrast with previous approaches to the problem, we are able to do it by using field potentials that are considerably smoother than the ones of the doubly quadratic family of potentials. This is done without losing the capacity of writing exact analytical solutions. The resulting field configurations can be applied to the study of problems from condensed matter to braneworld scenarios.